Productivity improvement in the rubber production process using value stream mapping method to eliminate waste - Evan Haviana; Hernadewita Hernadewita (Operations Excellence: Journal of Applied Industrial Engineering, 2019)
This Journal is the research of object that engaged in Industry of rubber Company, the product are formed in the Gasket product for final assembly into Hard Disk Drive, the function is to protect the connector inside Hard Disc. The Company continue to develop products and improve productivity performance by trying to improve quality of service, production process, and delivery product to customer with minimal cost and on time. To reach that purpose, a good method to eliminate waste and identify activities that can affect the products value-added was found, its value stream mapping (VSM), who can help to identify the waste from information flow, material flow and or processes flow. For this researchVSM with the support by root cause analysis tool has able to identify the highest stoppages processes contributed at rubber production that can increase the productivity. Rubber material, curing and deflashing processes had been selected for the improvement project. The improvement result showed total change over time (Non value added) from those processes were seen to be reduced from 70% until 88,89%.